Isolasi dan Identifi kasi Senyawa Kimia Zat Anti Kanker dari Daun Kopasanda (Chromolaena odorata (L.)) - MUHAMMAD FITRAH; HENDIG WINARNO; PARTOMUAN SIMANJUNTAK (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
Isolation and identifi cation of chemical compound as anticancer from the leaves of Kopasanda (Chromolaena odorata L.) had been done. Extraction was conducted successfully with n-hexane, ethylacetate and ethanol by maceration, and by refl ux for water solvent. Fractionation of ethylacetate extract by column chromatography (SiO2). n-hexane-ethylacetate = 10:1 ~ 1:1; ethylacetate). n-hexaneethylacetate = 5:1) gave one pure isolated fraction fr. 5-3 with inhibition activity against leukemia cell line L1210 at concentration 1.515 ppm. Chemical structure determination was done based on spectral data interpretation of Infra Red, 1D NMR (1H, 13C) and 2D NMR (H-H COSY, HMQC and HMBC) and mass spectra (LC-MS). Pure isolated fraction fr. 5-3 was deducted as methyl ether naragenine.